2007
DOI: 10.1093/ajcn/86.5.1463
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of adhesion molecules and other inflammatory biomarkers after moderate wine consumption in healthy women: a randomized trial

Abstract: Moderate wine consumption is associated with beneficial effects on various inflammatory pathways related to endothelial activation in women. Probably because of its higher polyphenol content, red wine shows superior antiinflammatory effects than does white wine. Reducing low-grade inflammation and endothelial activation may be another potential mechanism by which alcoholic beverages exert their cardioprotective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 38 publications
3
92
1
1
Order By: Relevance
“…When 112 volunteers at increased cardiovascular risk were randomised to a low-fat or Mediterranean diet for 3 months, significantly reduced concentrations of plasma sICAM-1 and sVCAM-1 were observed in the latter group [35]. Investigators have also reported down-regulation of these adhesion molecules following 4 week red wine [36] and 8 week soy nut interventions [37]. Such positive findings contrast with those reported here and may be related to a number of factors.…”
Section: Discussioncontrasting
confidence: 87%
“…When 112 volunteers at increased cardiovascular risk were randomised to a low-fat or Mediterranean diet for 3 months, significantly reduced concentrations of plasma sICAM-1 and sVCAM-1 were observed in the latter group [35]. Investigators have also reported down-regulation of these adhesion molecules following 4 week red wine [36] and 8 week soy nut interventions [37]. Such positive findings contrast with those reported here and may be related to a number of factors.…”
Section: Discussioncontrasting
confidence: 87%
“…In addition, clinical studies have demonstrated that daily intake of wine reduces monocyte adhesion and circulating markers of inflammation Estruch et al 2004). Moreover, Sacanella et al (2007) showed a more potent effect of red wine versus white wine, possibly due to its higher anthocyanin content. A suppression of NFkB in white blood cells by red wine was suggested to play a key role in its anti-inflammatory effects (Blanco-Colio et al 2000).…”
Section: Resultsmentioning
confidence: 96%
“…Also, grape polyphenols may have a reducing effect in cardiac fibrosis, a process occurring in cases of hypertension (17) Thirty-five healthy women 4 weeks Red wine with 13·5 % ethanol and 1·9 g total polyphenols/l or white wine with 13 % ethanol and 0·31 g total polyphenols/l Agewall et al (2000) (18) Twelve healthy subjects Acute intake Red wine with 1·9 g total polyphenols/l and 12·5 % ethanol or dealcoholised red wine with 1·1 g total polyphenols/l (250 ml in all groups) Cross-over design Naissides et al (2004) (19) Seventeen postmenopausal women Acute intake Dealcoholised red wine with 2·2 g total polyphenols/l, white wine with 2·2 g total polyphenols/l or water Cross-over design Williams et al (2004) (20) Fourteen men with stable IHD Acute intake Red wine with 13·5 % ethanol and 1·2 g total polyphenols/l, white wine with 13 % ethanol and 0·2 g total polyphenols/l or non-alcoholic drink without polyphenols Cross-over design Pignatelli et al (2006) (21) Twenty healthy subjects 3 weeks Red wine with 12·5 % ethanol and 1·2 g total polyphenols/l or white wine with 12·5 % ethanol and 0·18 g total polyphenols/l Castilla et al (2008) (24) Thirty-two haemodialysed patients 2 weeks Red grape concentrate (100 ml/d ¼ 600 mg total polyphenols/d), 800 IU (20 mg) vitamin E/d or both De Rijke et al (1996) (25) Twenty-four healthy subjects 2 weeks, then 4 weeks with different treatments (33) Nine hypercholesterolaemic and eight normocholesterolaemic subjects (45) Hypertensive men 8 weeks Grape juice with 2·1 g total polyphenols/l or placebo (11 ml/kg weight per d in all groups) Ward et al (2005) (46) Hypertensive subjects 6 weeks Vitamin C, polyphenols from red grape seeds (1 g/d), both or control Chou et al (2001) (47) Fifteen healthy subjects 1 week Extract from grape peel with 5 % total polyphenols (600 mg extract/d) Matsuo et al (2001) (51) Six men Acute intake Red wine, ethanol, polyphenols from red wine Cross-over design Freedman et al (2001) (52) Twenty healthy volunteers 2 weeks Purple grape juice (7 ml/kg weight per d) Boban et al (2006) (53) Nine men Acute intake Red wine, dealcoholised red wine, polyphenols from red wine, ethanol -water solution, water Cross-over design Whelan et al (2004) (10...…”
Section: Effects On Blood Pressure: Endothelial Functionmentioning
confidence: 99%